IMPROVING STUDENTS’ LEARNING OUTCOMES THROUGH THE APPLICATION OF AN INTERACTIVE MULTIMEDIA ON HUMAN EXCRETION SYSTEM MATERIAL - Aini Habibah; M Budiyanto; Enny Susiyawati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
The research aimed to describe the improvement of students learning outcomes through the application of interactive multimedia on human excretion system material. The research design used in this study was One Group Pretest-Posttest Design. This research was conducted in class VIII A and VIII D at SMPN 6 Gresik by involving 50 students. The method used in this study is the test method. The N-gain score obtained by class VIII A was 16% of students categorized as medium and 84% of students categorized as high, whereas the N-gain results obtained by class VIII D of students who were categorized as moderate by 12% and students categorized as high by 88%. The significance probability obtained by class VIII A and VIII D is 0,000 which indicates a significant increase in pretest and posttest. The average skills assessment obtained by class VIII A was 88.57 for the first meeting and 90 for the second meeting. In class VIII D the first meeting the average assessment of skills was 85.57 and 89.28 in the second meeting. Based on the results of the research, it concluded that the application of interactive multimedia on human excretion system material improved students learning outcomes.